Prolonged Elevation of Arterial Stiffness Following Peak Aerobic Exercise in Individuals With Chronic Stroke - Noguchi, Kenneth S.; Moncion, Kevin; Wiley, Elise; MacDonald, Maureen J.; Richardson, Julie; Roig, Marc; Tang, Ada (Frontiers in Physiology, 2021)
Background. Stroke is a highly disabling condition and is the second leading cause of death globally. Engaging in aerobic exercise is important for the prevention of a recurrent stroke through improving markers of cardiovascular health such as blood pressure and arterial stiffness. While higher intensities of aerobic exercise generally elicit greater cardioprotective effects, little is known about the acute cardiovascular effects of a single session of high intensity aerobic exercise in people with stroke. The objective of this study was to model the recovery of arterial stiffness (carotid-femoral pulse wave velocity, cfPWV), heart rate and blood pressure following peak intensity aerobic exercise in individuals with chronic stroke. Methods. Ten participants with chronic stroke (mean±SD age=56.9±11.8 years, median [IQR] years post-stroke= 2.9 [1.9]) performed a symptom-limited cardiopulmonary exercise test (CPET) on a recumbent stepper. Before the CPET, resting cfPWV, heart rate and blood pressure were measured. Immediately following the CPET, all outcomes were measured again continuously for 20 minutes to use all available observations (n=245 observations) and capture any potential non-linear changes. Mixed model analyses were then applied to model post-exercise changes of cfPWV, heart rate and blood pressure. Results. cfPWV was increased from rest following the CPET (9.0±0.53 m/s to 9.9±0.52 m/s, p<0.001) and remained elevated for 20 minutes into post-exercise recovery, independent of heart rate (p=0.001). Heart rate also increased from baseline (71.2±3.2 bpm to 77.4±3.1 bpm, p<0.001) and remained elevated for 10 minutes post-exercise (p<0.001). Finger systolic blood pressure was reduced from rest (117.3±4.7 mmHg to 111.8±4.6 mmHg, p<0.001) and remained reduced for 15 minutes after exercise (p<0.001). There were no significant differences in finger diastolic or mean arterial pressures from rest. Conclusion. This was the first study to capture continuous changes in cfPWV following peak aerobic exercise in any clinical population. The present study revealed that cfPWV is elevated for 20 minutes after peak aerobic exercise in individuals with stroke, which was independent of heart rate. These findings suggest there may be autonomic imbalances in large arteries following peak intensity aerobic exercise in individuals with stroke.